Mutation Status and Immunohistochemical Correlation of KRAS, NRAS, and BRAF in 260 Chinese Colorectal and Gastric Cancers - Yang, Qiwei; Huo, Sibo; Sui, Yujie; Du, Zhenwu; Zhao, Haiyue; Liu, Yu; Li, Wei; Wan, Xin; Liu, Tongjun; Zhang, Guizhen (Frontiers in Oncology, 2018)
KRAS, NRAS and BRAF are kinases involved in the RAS-RAF-MAPK signaling pathway and also potential tumor-driven genes. Patients with KRAS/NRAS/BRAF mutations are resistant to anti-EGFR monoclonal antibody therapy. The main purpose of this study is to investigate the mutation status and distribution of KRAS/NRAS/BRAF in Chinese colorectal and gastric cancers, and to explore the histopathological changes and related immunohistochemical marker changes caused by these mutations. The mutation status of KRAS (exons 2, codon 12/13), NRAS (exons 2/3/4, codon 12/13/59/61/117/146) and BRAF (exons 15, codon 600) were detected by amplification refractory mutation system polymerase chain reaction (ARMS-PCR) in 86 colon cancer, 140 rectal cancer and 34 gastric cancer tissues. Then, the frequencies and distribution of KRAS/NRAS/BRAF mutations were described in detail. Furthermore, the relationship between KRAS/NRAS/BRAF mutations and the features of histopathological and related immunohistochemical markers were analyzed. The results showed that KRAS/NRAS/BRAF mutation rates in colon cancer were 44.2, 1.2, and 3.5%; in rectal cancer were 37.1, 4.3, and 0.7%; in gastric cancer were none, none and 2.9%. The mutation rate of KRAS in female (48.8%) is significantly higher than that of male (27.8%), and the mutation rate increased with the higher degree of differentiation. Additionally, the mutation rate of BRAF detected by ARMS-PCR (1.77%) was significantly lower than that by immunohistochemistry (4.11%). It also showed that the KRAS/NRAS/BRAF mutation status had a certain relationship with the expression of some immunohistochemical markers. This study provides more data support for clinical research on KRAS/NRAS/BRAF mutation in CRCs or gastric cancers.